Memory B cell development in response to mRNA SARS-CoV-2 and nanoparticle immunization in mice - Marie Wiatr; Zijun Wang; Marie Canis; Brianna Hernandez; Anna Gazumyan; Gabriela S. Silva Santos; Sadman Shawraz; Songhee Lee; Paul D. Bieniasz; Theodora Hatziioannou; Frauke Muecksch; Michel C. Nussenzweig (Proceedings of the National Academy of Sciences, 2026)
Nanoparticle immunogens excel at rapidly inducing high levels of circulating antibodies and are being deployed as part of several novel vaccines. However, their ability to elicit memory B cell responses is less well understood. Here, we compared serologic and memory B cell responses after prime boost vaccination with either SARS-CoV-2 Wuhan-Hu-1 mRNA vaccine, or protein nanoparticles: SARS-CoV-2 B.1.351 homotypic containing a single receptor binding domain (RBD); (homotypic beta) or a combination of different Sarbecovirus RBDs (mosaic 8b), respectively. The memory B cells elicited by the 3 vaccine regimens showed closely related antibody sequences, similar levels of somatic mutation, and clonal diversity. The breadth of serologic responses elicited by the mosaic nanoparticles was comparable to the homotypic nanoparticle and superior to the mRNA vaccine for some mismatched strains. However, serum neutralizing titers to SARS-CoV-2 were highest after mRNA vaccination. The three vaccines elicited memory B cells that produced antibodies specific to a broad range of epitopes on the RBD that differed in a way that may reflect epitope masking. Monoclonal antibodies derived from memory B cells elicited by the mosaic 8b nanoparticle showed greater breadth against a panel of SARS-CoV-2 variants and SARS-CoV.